2015
DOI: 10.1021/acs.jpca.5b06593
|View full text |Cite
|
Sign up to set email alerts
|

An Isolated Complex of Ethyne and Gold Iodide Characterized by Broadband Rotational Spectroscopy and Ab initio Calculations

Abstract: A molecular complex of C2H2 and AuI has been generated and isolated in the gas phase through laser ablation of a gold surface in the presence of an expanding sample containing small percentages of C2H2 and CF3I in a buffer gas of argon. Rotational, B0, centrifugal distortion, ΔJ and ΔJK, and nuclear quadrupole coupling constants, χaa(Au), χbb(Au) - χcc(Au), χaa(I), and χbb(I) - χcc(I), are measured for three isotopologues of C2H2···AuI through broadband rotational spectroscopy. The complex is C2v and T-shaped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…A theoretical study on the resonance character of bonding in B ⋅⋅⋅ M−X systems (M=Cu, Ag, Au; X=F, Cl, Br, CH 3 , CF 3 ; B=CO, H 2 O, H 2 S, C 2 H 2 , C 2 H 4 ) is partly in line with this study, since among different interactions also the Au ⋅⋅⋅ π contacts are considered here . One can also mention the T‐shaped FLi ⋅⋅⋅ C 2 H 4 and IAu ⋅⋅⋅ C 2 H 2 structures, the latter of which was analyzed both theoretically and experimentally by broadband rotational spectroscopy . Several examples are more or less related to this study: the association reactions leading to Ag + ⋅⋅⋅ C 2 H 2 and Ag + ⋅⋅⋅ (C 2 H 2 ) 2 , which were studied by high‐pressure mass spectrometry, the analysis of crystal structures in which Ag + ⋅⋅⋅ (C 2 H 2 ) n ( n ≤4) clusters were detected with T‐shaped Ag + ⋅⋅⋅ C 2 H 2 arrangements, and earlier experimental studies on the Ag(C 2 H 4 ) 3 + ions in the solid state …”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…A theoretical study on the resonance character of bonding in B ⋅⋅⋅ M−X systems (M=Cu, Ag, Au; X=F, Cl, Br, CH 3 , CF 3 ; B=CO, H 2 O, H 2 S, C 2 H 2 , C 2 H 4 ) is partly in line with this study, since among different interactions also the Au ⋅⋅⋅ π contacts are considered here . One can also mention the T‐shaped FLi ⋅⋅⋅ C 2 H 4 and IAu ⋅⋅⋅ C 2 H 2 structures, the latter of which was analyzed both theoretically and experimentally by broadband rotational spectroscopy . Several examples are more or less related to this study: the association reactions leading to Ag + ⋅⋅⋅ C 2 H 2 and Ag + ⋅⋅⋅ (C 2 H 2 ) 2 , which were studied by high‐pressure mass spectrometry, the analysis of crystal structures in which Ag + ⋅⋅⋅ (C 2 H 2 ) n ( n ≤4) clusters were detected with T‐shaped Ag + ⋅⋅⋅ C 2 H 2 arrangements, and earlier experimental studies on the Ag(C 2 H 4 ) 3 + ions in the solid state …”
Section: Introductionsupporting
confidence: 79%
“…[20] One can also mention the T-shaped FLi···C 2 H 4 [21] andI Au···C 2 H 2 structures, the latter of which was analyzed both theoretically and experimentally by broadband rotational spectroscopy. [22] Several examples are more or less related to this study:t he association reactions leading to Ag + ···C 2 H 2 and Ag + ···(C 2 H 2 ) 2 ,w hich were studied by high-pressurem ass spectrometry, [23] the analysis of crystal structuresi nw hichA g + ···(C 2 H 2 ) n (n 4) clusters were detected with T-shaped Ag + ···C 2 H 2 arrangements, [24] and earlier experimental studies on the Ag(C 2 H 4 ) 3 + ions in the solid state. [25] The ab initio calculations were supported by the Quantum Theoryo fA tomsi nM olecules [26] and energy decomposition analysis( EDA) [27,28] to deepen the understanding of the nature of the interactions in these systems.…”
mentioning
confidence: 99%
“…Computational evidence was also given for the possibility of the existence of stable HFÁ Á ÁAu-OH and H 2 OÁ Á ÁAu-OH complexes. 16 Legon and coworkers [17][18][19][20][21][22][23] characterized a series of complexes BÁ Á ÁMX (B = N 2 , C 2 H 2 , C 2 H 4 , (CH 2 ) 3 , H 2 O, H 2 S, PH 3 , or NH 3 ; M = Cu, Ag, Au; X = F, Cl, Br) by means of rotational spectroscopy and ab initio calculations, and found that the BÁ Á ÁMX complexes are isomorphous with the hydrogen-or halogen-bonded counterparts, and exhibit some similar properties with hydrogen bonds. The name 'coinage-metal' noncovalent bond 23 was suggested for the non-covalent interaction in BÁ Á ÁMX, by analogy with hydrogen and halogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Contributions to the calculated ab initio geometry of AuI were discussed in detail in a previous work. 58 It was shown that extrapolation beyond CCSD(T)(F12*)/AVTZ to the basis set limit does not yield a significant change in the r(AuI) distance calculated for free AuI. However, the inclusion of core-valence correlation reduces this bond length by 0.014 Å.…”
Section: B Molecular Geometrymentioning
confidence: 99%